KERJASAMA INDONESIA – NORWEGIA MELALUI SKEMA REDUCING EMISSIONS FROM DEFORESTATION AND FOREST DEGRADATION (REDD+) DALAM UPAYA PENYELAMATAN HUTAN INDONESIA - Nadhea Lady (Universitas Komputer Indonesia, 2018)
This study used qualitative research type. The research method used is descriptive analysis techniques. Most of the data collected through the literature, searching websites, and interviews. Those data were analyzed by theory approach based on International Relations, Foreign Policy, International Cooperation, International Agreement, and Environmental. The results of this study indicate that the cooperation between Indonesia – Norway through the REDD scheme is poured into the form of a Letter of Intent (LoI) agreed on three phases in order to save Indonesia’s forest despite undergoing a new stage in the first phase, this cooperation has resulted although not significantly.